Diagnostic accuracy of single-voided urine protein/ creatinine ratio for proteinuria assessment in children with nephrotic syndrome - Devie Kristiani; Pungky Ardani Kusuma; Purnomo Suryantoro (Paediatrica Indonesiana, 2009)
Background Measurement of protein excretion is not onlyused for diagnostic purpose but also to monitor disease severityand prognosis in children with nephrotic syndrome (NS).The common method to measure proteinuria is 24-hour urinecollection. However, 24-hour urine collection is cumbersome,time consuming, and tedious. An alternative simplified methodis the measurement of protein/creatinine ratio in single-voidedurine specimens.Objective The aim of this study was to determine whether urineprotein/creatinine ratio is accurate to predict pathologic (> 100mg/m2/day) and massive proteinuria (> 1 g/m2/day).Methods Seventy single voided and 24-hour urine specimenswere collected from children aged 3-18 years. The relationshipbetween urinary protein/creatinine ratio and total daily proteinexcretion was calculated using correlation and linear regressionanalysis. Diagnostic test was conducted to estimate the accuracyof protein/creatinine ratio for the diagnosis of pathologic andmassive proteinuria in NS.Results Correlation coefficient between quantity of protein in24-hour urine specimens and protein/creatinine ratio in singlevoided urine specimens was 0.96 (R2=0.93). Both sensitivity and specificity of urinary protein/creatinine ratio were 87% in diagnosing pathologic proteinuria, whereas the sensitivity and specificity of the ratio to predict massive proteinuria were 88% and 91%, respectively.Conclusion The urinary protein/creatinine ratio in single voidedurine specimen has a good accuracy to predict pathologic andmassive proteinuria in children with NS aged 3-18 years.